2010
DOI: 10.1097/qai.0b013e3181e583da
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Risk of HIV Disease Progression and Death in Ugandan Children Not Eligible for Antiretroviral Therapy

Abstract: Background Increasing numbers of HIV-infected children not yet eligible for antiretroviral therapy (ART) are entering health care in Africa. We sought to characterize the risk of short-term disease progression in this population. Methods In a cohort of HIV-infected ART-naive and -ineligible Ugandan children >1 year old, the rates of clinical/immunologic progression within 2 years were assessed using Kaplan–Meier survival analysis and multivariate Cox proportional-hazards modeling. Results Among 192 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…As shown by the literature, significant clinical events do occur in HIV-infected children and adolescents even before meeting the previous guidelines [19, 20]. Our data therefore support the 2013 WHO consolidated guidelines recommending early ART initiation for children less than five years old regardless of CD4 cell count [41].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As shown by the literature, significant clinical events do occur in HIV-infected children and adolescents even before meeting the previous guidelines [19, 20]. Our data therefore support the 2013 WHO consolidated guidelines recommending early ART initiation for children less than five years old regardless of CD4 cell count [41].…”
Section: Discussionsupporting
confidence: 84%
“…As an illustration, retention varied from 71% to 95% and 62% to 93% at 12 and 24 months, respectively, among children and adolescents in ART programmes in several countries of SSA [ 18 ]. A prior study in Uganda showed that even with frequent CD4 monitoring, HIV-infected children experienced significant clinical events while ineligible for ART according to the 2006 WHO guidelines [ 19 ]. Another study in Uganda showed that mortality was highest among HIV-infected children under two years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These 'longterm survivors' have particular needs that are usually not adequately met in resource-limited settings. Whilst they do not have the same mortality risk as younger children as shown by this study and others (Charlebois et al 2010;Fenner et al 2010), they face significant morbidities, including risk of poor physical and neurodevelopmental growth, poor sexual maturation and risk of chronic lung disease (Smith et al 2012). Furthermore, from a social perspective, this group of children has a higher likelihood of being orphaned and often struggles with challenges in their home life as well as at school, which has implications for their adherence to treatment (Williams et al 2006).…”
Section: Discussionmentioning
confidence: 50%
“…Whilst they do not have the same mortality risk as younger children as shown by this study and others (Charlebois et al . ; Fenner et al . ), they face significant morbidities, including risk of poor physical and neurodevelopmental growth, poor sexual maturation and risk of chronic lung disease (Smith et al .…”
Section: Discussionmentioning
confidence: 99%
“…2–4 A delay in antiretroviral therapy (ART) initiation also increases the risk of morbidity and mortality among children. 58…”
Section: Introductionmentioning
confidence: 99%